MAHALLA SYSTEM FOR ESTIMATING AGRICULTURAL AND LIVESTOCK PRODUCTION - Qulmatova Sayyora Safarovna (Modern American Journals, 2025)
A number of difficulties arise in modeling household decision-making in developing countries. First, the real structure and organization of a household are not adequately represented in the example of a nuclear household with a common place of residence and joint decisions on the consumption of public goods. Many scholars and practitioners around the world pay great attention to the current state of mahalla production and trends in it. However, the issue of choosing a strategy for the development of household areas has not been sufficiently studied. This creates problems for a comprehensive assessment of the state and potential of regional mahalla development. The cluster analysis method was used to group areas by the level of development of potential.The level of development of regional clustering analysis was examined using the K-means method. Clustering can be used to analyze and reassess the development of production in districts.
Keywords: Households, regions, cluster analysis, K-means method.